Challenges and trends of automation of logistics processes in bond warehouses using industry 5.0 concepts - Сhala, O. O.; Kryvenko, D. O. (ХНУРЕ, 2025)
the paper studies the current state of the issue of automation of bonded logistics warehouses. It is noted that, taking into account the concept of Industry 5.0 and an integrated approach, it is possible to carry out significant modernization in such structures. The main reason preventing such an upgrade is the imperfection of software modules that combine monitoring and operational regulation of processes at a logistics warehouse enterprise. The solution to the issue may be the improvement and expansion of computer-integrated systems to coordinate the functioning of individual subsystems.
Keywords: utomation; robotic; logistics